This moment on Earth today's new environmentalists and their vision for the future - Kerry, John 1943- (PublicAffairs, 2007)
A celebration of courageous American innovators who are transforming the way we protect and care for the world we live in. The environment, and the movement that grew up to protect it, is under concerted and purposeful attack. The need for solutions to pressing environmental problems grows more urgent each day. Teresa Heinz Kerry and Senator John Kerry traveled across the country in a national campaign to see at first hand how these issues unite people across party and ideological lines. From the San Juan Basin to the Gulf of Mexico to the South Bronx, from mothers on Cape Cod to Colorado ranchers, they found a vibrant coalition of people and communities deploying ingenuity, technology, and sheer will power to save the world they know and love. Here, the Kerrys shine the spotlight on an inspiring cross-section of these new environmental pioneers.--From publisher description.